Case Study Report: Nursing Intervention to Improve Physical Mobility in a Postoperative Tibial Fracture Patient - Suwanto, Agus Wiwit; Purwaningsih, Endang; Wiratmoko, Heru; Octavia, Nataya Rizka (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Surgery is an invasive medical procedure performed to restore the anatomy and physiology of impaired body organs. One type of surgery is fracture surgery, which aims to restore the anatomy and physiology of bones that are broken for various reasons. The purpose of this study was to provide nursing care to a post-operative tibial fracture patient with a physical mobility disorder in the Flamboyan Room of Dr Harjono Ponorogo Hospital. This study used a descriptive design with a case study approach involving a participant who met the criteria. Data collection techniques included interviews and observation of muscle strength and range of motion (ROM) values. The results of the assessment found that the patient had grade 2 muscle strength in the left extremity, and the ROM value was reduced. The nursing diagnosis was Physical Mobility Disorder. Nursing interventions according to SIKI included early mobilisation and early ambulation for seven days. The evaluation results showed that muscle strength increased from grade 2 to grade 5 by the sixth day, and the ROM value improved to reach the average normal limit by the sixth day. ROM exercises and the use of crutches were effective in improving physical mobility. ROM exercises are effective for improving physical mobility because they can reduce pain levels, thus decreasing concerns related to mobility.